Improving middle and high school students' comprehension of science texts - Brandi E. JOHNSON; Karen M. ZABRUCKY (International Electronic Journal of Elementary Education, 2011)
Throughout the United States, many middle and high school students struggle to comprehend science texts for a variety of reasons. Science texts are frequently boring, focused on isolated facts, present too many new concepts at once, and lack the clarity and organization known to improve comprehension. Compounding the problem is that many adolescent readers do not possess effective comprehension strategies, particularly for difficult expository science texts. Some researchers have suggested changing the characteristics of science texts to better assist adolescent readers with understanding, while others have focused on changing the strategies of adolescent readers. In the current paper, we review the literature on selected strategy instruction programs used to improve science text comprehension in middle and high school students and suggest avenues for future research.